PREVALENCE OF MULTIDRUG-RESISTANT ORGANISMS IN HOSPITAL-ACQUIRED PNEUMONIA AMONG ICU PATIENTS AND ITS CLINICAL OUTCOMES: A PROSPECTIVE OBSERVATIONAL STUDY. - Suryaman, Chintapalli; Gangaram, Vennela; Dr R B Swathi; Sonica, Vepuri Pavitra (Student’s Journal of Health Research Africa, 2025)
Background Multidrug-resistant organisms (MDROs) are a growing concern in hospital-acquired pneumonia (HAP) among ICU patients, contributing to increased morbidity, mortality, and healthcare costs. This study aims to evaluate the prevalence, resistance profiles, clinical outcomes, and impact of antibiotic therapy on ICU patients with MDRO-related HAP. Methods A total of 100 ICU patients diagnosed with HAP were included in the study. The prevalence of MDROs, resistance profiles of the organisms, and clinical outcomes were assessed. Data on mechanical ventilation, ICU stay duration, mortality rates, and antibiotic therapy were collected and analyzed. The study also examined co-infections and complications in patients with MDRO infections. Results 100 ICU patients were included, with a mean age of 58.4 ± 12.3 years; 60% were male and 40% were female. The majority of patients had comorbidities such as diabetes mellitus (45%), chronic obstructive pulmonary disease (33%), and hypertension (30%). The most common MDROs identified were Klebsiella pneumoniae (24%), Pseudomonas aeruginosa (21%), and Acinetobacter baumannii (19%). These organisms exhibited high resistance to third-generation cephalosporins, carbapenems, and fluoroquinolones. Patients with MDRO infections had significantly higher rates of mechanical ventilation (69% vs. 28%), prolonged ICU stays (62% vs. 14%), and a higher mortality rate (35% vs. 12%) compared to non-MDRO patients. Appropriate antibiotic therapy improved clinical outcomes, with a 40% improvement rate in the proper therapy group. Co-infections, including Candida albicans (12%) and Staphylococcus aureus (10%), were common in MDRO-infected patients. Conclusion MDROs significantly impact the clinical outcomes of ICU patients with HAP, leading to increased mechanical ventilation, longer ICU stays, and higher mortality. Appropriate antibiotic therapy plays a critical role in improving patient outcomes. Recommendations Early MDRO detection in ICU-HAP patients requires surveillance, rapid diagnostics, strict infection control, and antimicrobial stewardship to prevent resistance.